New genetic mutations in a Chinese child with Ehlers-Danlos syndrome-like spondyloepimetaphyseal dysplasia: A case report - Han, Shu; Xu, Xuan; Wen, Jie; Wang, Jianzhou; Xiao, Sheng; Pan, Li; Wang, Jiang (Frontiers in Pediatrics, 2022)
Background: Ehlers-Danlos syndrome(EDS) spinal deformity type 2 has similar clinical features as Spondyloepimetaphyseal dysplasia with joint laxity,type 1(SEMDJL1). They have similar clinical manifestations and a similar genetic basis, both of which can be caused by mutations in the B3GALT6 gene. Hence, genetic screening and careful clinical examination are the key to the differential diagnosis of these two diseases. Case presentation: A 4 months old baby boy was admitted to our hospital in order to find the causes of developmental delay.Clinical examination revealed that the child was delayed, with excessive range of motion of joints, patent foramen ovale, and was accompanied by skin aging, and the child was suspected to suffer from Ehlers-Danlos syndrome (EDS). However, unlike EDS, the child had normal muscle tension, and at the same time had spinal deformity, mild kyphosis, widened right hip joint space, as well as special face, joint laxity and slender fingers, which were typical characteristics of SEMDJL1. Gene analysis showed two suspicious mutations in the B3GALT6 gene: c.808G>A(p.G270S) and c.942G>C(p.W314C), which were verified to be compound heterozygous mutations by analyzing genes in his parents. This mutation was not included in the HGMD, clinvar and other mutation databases, and thus was a newly discovered mutation. Conclusion: With clinical analysis and genetic analysis, this study for the first time reported one Chinese case with EDS-like SEMDJL1.Two pathogenic mutations were discovered in B3GALT6 gene:c.808G>A(p.G270S) and c.942G>C(p.W314C).